The Impact of Epidural Analgesia on the Rate of Thromboembolism without Chemical Thromboprophylaxis in Major Oncologic Surgery. Issue 6 (June 2018) - Manguso, Nicholas; Hong, Jenny; Shouhed, Daniel; Popelka, Sarah; Amersi, Farin; Hemaya, Emad; Sibert, Karen; Silberman, Allan W.
Patients with abdominopelvic cancers are at increased risk of venous thromboembolism (VTE) due to their malignancy. We evaluated outcomes and the rate of VTE in patients undergoing abdominopelvic surgery for malignancy with preoperative epidural analgesia without postoperative chemical VTE prophylaxis. A retrospective review between 2009 and 2015 identified 285 patients with malignancy who underwent abdominopelvic surgery by a single surgeon (AWS). Lower extremity venous duplex scans (VDS) were performed preoperatively and before discharge. Demographics, procedures, and VTE outcomes were reviewed. The median age was 66 years. The average operative time was 315 minutes. All patients ambulated on postoperative day (POD) one or two. Epidural catheters (ECs) were removed on postoperative day four or five. No patient received VTE prophylaxis while an epidural catheter was in place. Preoperative lower extremity VDS revealed above-knee deep vein thrombosis (DVT) in seven patients (2.5%). Postoperative lower extremity VDS revealed acute DVT in 24 patients (8.4%): nine (3.2%) above-knee and 15 (5.2%) below-knee. The nine patients with above-knee DVT were anticoagulated after epidural removal. No patient developed a pulmonary embolism. Our data suggest that patients undergoing major open operations with epidural analgesia have low rates of DVT and may obviate the need for chemical prophylaxis. However, larger studies are required to determine the overall effects of epidural analgesia on the development of DVTs postoperatively.